WILL INDIA BECOME A FULL-FLEDGED PARTICIPANT IN THE BIG GAME IN CENTRAL ASIA? - KOMISSINA, Irina (CENTRAL ASIA AND THE CAUCASUS, 2008)
Most analysts now agree that Central Asia has become an arena of the Big Game currently being played by the leading world and regional leaders. Nor has India been left on the sidelines, especially since it has clearly outgrown the role of generally accepted leader of the South Asian subcontinent of late and is making its claims to something more. Central Asia is geographically close to India and has common deep historical roots with this country; so, its presence in the zone of Indian strategic interests comes as no surprise. This is also promoted by the significant potential for cooper ation and good-neighborly relations that accumulated over the long years of traditional Indian Soviet cooperation. Another important factor is that India is trying to prevent Pakistan—its permanent rival in the South Asia Region—from unilaterally increasing its influence on the Central Asian states where a power vacuum rapidly filled by numerous contenders formed after Russia withdrew. So the Indian leadership entrusted its foreign policy and foreign economy departments with the task of developing targeted relations and strengthening cooperation with the countries of the Central Asian Region. The so called New Silk Road of Indian Foreign Policy became an important step in this direction.1 The exchange of visits between the heads of state and numerous delegations of different levels and vectors clearly demonstrates Delhi’s foreign policy priorities. The development of so-called people-to-people diplomacy is very important in the Central Asian vector.